Peran Kesetaraan Gender di Masa Pandemi - Erny Hutabarat; Danielle Nadine Anakotta; Xie Haozhe (ACADEMICS IN ACTION Journal of Community Empowerment, 2021)
During this pandemic, there are many issues that have been neglected due to compelling conditions, one of the issues that has begun to be neglected is gender. Through the 4psace.foryou program we want to educate our followers to know about gender and the forms of gender discrimination during this pandemic. The aim of our program is to educate and bring awareness about our forms that respect gender. Our method for educating his followers program is to create a campaign on Instagram with 3 main topics. This program is also protected by a Content Creator named Iwan Kurniawan. This 4space.foryou campaign program was successful in getting 100 participants and we managed to influence our followers through the content we created on Instagram by gathering aspirations and from our 100 followers. This program has also succeeded in bringing influence to Iwan Kurniawan and his followers on Instagram. Overall, the objectives and benefits of this program have been achieved, and we can prove it through the data that has been collected.